Assessing the Relevance of Information Sources for Modelling Student Performance in a Higher Mathematics Education Course - Adrián Pérez-Suay; Ricardo Ferrís-Castell; Steven Van Vaerenbergh; Ana B. Pascual-Venteo (MDPI AG, 2023)
In recent years, most educational institutions have integrated digital technologies into their teaching-learning processes. Learning Management Systems (LMS) have gained increasing popularity, particularly in higher education, due to their ability to manage teacher-student interactions. These systems store valuable information which describes students' behaviour throughout a course. These data can be utilised to construct statistical models that represent learner behaviour within an online LMS platform. In this study, we aim to compare different sources of information and, more ambitiously, to provide insights into which source of information is most valuable for inferring student performance. The considered sets of information come from (i) the Moodle LMS; (ii) socio-economic data about students acquired from a survey; and (iii) subject marks achieved throughout the course. To determine the relevance of the incorporated information, we use artificial intelligence (AI) methods, and we report the importance measures of four state-of-the-art methods. Our findings indicate that the selected methodology is suitable for making inferences about student performance while also shedding light on model decisions through explainability.